2022
DOI: 10.4081/jphr.2021.2742
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Smartphone-Based Perioperative Nursing Intervention: Prayer, Education, Exercise Therapy, Hypnosis, and Music toward Pain, Anxiety, and Early Mobilization on Cardiac Surgery

Abstract: Background: Cardiac surgery can elicit both physical and psychological responses. Prayer, exercise therapy, education, hypnosis, and music are expected to be able to overcome pain, anxiety, and immobilization in the cardiac surgery. This study was to create a smartphone-based peri-operative nursing intervention model that was able to reduce pain, anxiety, and increase early mobilization cardiac surgery patients.Design and Methods: This study consisted of three stages. The first stage was research and developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…In the intraoperative stage, smartphones are used for hemodynamic monitoring. In the post-operative stage, smartphones are used for monitoring surgical wounds, detection of Atrial Fibrillation (AF) and other rhythm-related complications after cardiac surgery, and early mobilization intervention media (Awaludin, Nurachmah, Soetisna, & Umar, 2022;Brusco, 2010;Kulendran et al, 2014;Lamberigts et al, 2021;Pluta et al, 2022;Soangra & Lockhart, 2021). The benefits posed by smartphone application technology in heart surgery are also for the delivery of health services, patient outcomes, as well as clinical and lay education.…”
Section: Discussionmentioning
confidence: 99%
“…In the intraoperative stage, smartphones are used for hemodynamic monitoring. In the post-operative stage, smartphones are used for monitoring surgical wounds, detection of Atrial Fibrillation (AF) and other rhythm-related complications after cardiac surgery, and early mobilization intervention media (Awaludin, Nurachmah, Soetisna, & Umar, 2022;Brusco, 2010;Kulendran et al, 2014;Lamberigts et al, 2021;Pluta et al, 2022;Soangra & Lockhart, 2021). The benefits posed by smartphone application technology in heart surgery are also for the delivery of health services, patient outcomes, as well as clinical and lay education.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of preprocedural anxiety is reported to be approximately 80%, leading to hypertension and tachycardia, which can lead to bleeding and other complications. 2 As the authors have also identified, this anxiety can have an impact on long-term mental health. 1 However, I have not seen a rise in repeat ablations or cardioversions among the more anxious or depressed patients.…”
Section: Ear Editorsmentioning
confidence: 95%
“…The smartphone application included music therapy, prayer, patient education, and hypnosis. 2 I hope you will be pleased to know the impact the article prepared by Fitzgerald et al 3 has had on myself and my electrophysiology team, as well as the preprocedural and postprocedural areas. Your authors have helped us become more aware of the mental health challenges our patients experience and how they may impact their quality of life and outcomes.…”
Section: Ear Editorsmentioning
confidence: 98%
See 2 more Smart Citations